The institutional ownership, auditor characteristics and KAM disclosure: Evidence from emerging markets - Sumartono, Sumartono; Ardianto, Ardianto (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to explore the relationship between Institutional Ownership (IO), auditor characteristics (Big 4), and Key Audit Matter (KAM) disclosure. It also analyzes IO and KAM disclosure by dividing the sample into subgroups based on the percentage of IO amount above or below the average institutional ownership of the firms. Data was obtained from annual reports collected from companies listed on the Indonesia Stock Exchange (IDX) in 2022 through the idx.co.id website using 649 observations, and analyzed using regression while content analysis was used to measure KAM disclosure. The research findings show that Big 4 has a positive relationship with KAM disclosure. However, no significant evidence was found to suggest that IO has a significant relationship with KAM disclosure during the observation period. This study underscores that the adoption of Auditing Standard (SA) 701 as part of an international initiative may improve financial reporting transparency, especially in firms audited by the Big 4 which tend to provide more comprehensive KAM disclosures. This research provides an important contribution for regulators, auditors, and policymakers to refine the corporate governance framework and auditing standards, ultimately leading to improved transparency and audit quality in emerging markets such as Indonesia. This study recommends refining KAM communication guidelines to further enhance transparency and reduce information asymmetry, especially for non-Big 4 firms and suggests that policymakers need to strengthen corporate governance mechanisms to improve audit quality.